Peningkatan Kualitas Fisika Tanah Guna Efisiensi Air Melalui Pengkayaan Media Tanam Dengan Kompos Plus Pada Budidaya Tanaman Jagung Manis: Peningkatan Kualitas Fisika Tanah Guna Efisiensi Air Melalui Pengkayaan Media Tanam Dengan Kompos Plus Pada Budidaya Tanaman Jagung Manis - Darso Sugiono; Vera O Subardja; Briljan Sudjana (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2018)
Soil physical characteristics play an important role in nutrient and water availability for plants. Dryland consist of marginal land has the potential to use as corn cultivation area. This research conducted in the shade house of PT. Pupuk Kujang Cikampek. Research started with producing of compost plus by using fungus cultivation medium enriched with Azotobacter sp. and Pseudomonas sp. Research designed using Factorial RBD. The first factor was doses of organic fertilizer consisting of without compost plus (0 tons compost plus ha-1), 50% recommended dosage (10 tons compost plus ha-1) and 100% recommended dosage (20 tons plus compost ha-1). The second factor was water volume with 4 levels of treatment consist of 25% volume of water field capacity, 75% volume of water field capacity, 100% volume of water field capacity and 50% volume of water field capacity. Calculation of water field capacity will be carried out with the gravimetric method. Physical characteristics of the soil were analyzed by referring to the analysis method of the Indonesian Center for Agricultural Research and Development in 2006. The results showed that the use of compost plus improved the quality of soil physical characteristics of corn cultivation in dry land such as water content, bulk density, soil porosity. The use of compost plus is able to substitute the water needs of corn plants was seen by the growth and yield of corn plants under water stress conditions with the addition of compost plus still have good performance and yield.